The Influence of Self-Determination,Organizational Culture, Work Motivation, and Job Satisfaction on the Performance of Principals of State Primary School in Aceh Besar District, Aceh - Hambali, Hambali; Zainuddin, Zainuddin; Darwin, Darwin (International Journal for Educational and Vocational Studies, 2020)
The performance of the principal of SD Negeri is the positive or negative behavior of the principal of SD in achieving SD goals. This study found that: (1) self-determination affects the work motivation of primary school principals by 25.3%; (2) organizational culture affects the work motivation of primary school heads in Aceh Besar District by 27.9%; (3) self-determination affects the job satisfaction of primary school principals in Aceh Besar District by 27.1%; (4) organizational culture affects the job satisfaction of primary school principals in Aceh Besar District by 21.5%; (5) self-determination affects the performance of primary school principals in Aceh Besar District by 20.2%; (6) organizational culture affects the performance of primary school principals in Aceh Besar District by 17.5%; (7) work motivation affects the performance of primary school principals in Aceh Besar District by 18.9%, and (8) job satisfaction affects the performance of primary school principals in Aceh Besar District by 24.5%. Based on the results of the study, it found that self-determination, organizational culture, work motivation, and job satisfaction had a positive and significant effect on the performance of the principal of SD Negeri in Aceh Besar District, Aceh Province. Keywords: Self-determination, Organizational Culture, Work Motivation, Job Satisfaction, Principal Performance.